The value of fairness : the story of Nellie Bly - Pileggi, Steve (La Jolla, Calif. : Value Communications, inc., 1977)
Demonstrates the value of fairness in the life of the turn-of-the-century journalist whose pen name was Nellie Bly.
Title on spine: Fairness.
Keywords: Bly, Nellie, -- 1864-1922 -- Juvenile literature; Bly, Nellie, -- 1864-1922.; Journalists -- United States -- Biography -- Juvenile literature; Journalists; Women -- Biography; Fairness